2001
DOI: 10.1385/endo:16:2:073
|View full text |Cite
|
Sign up to set email alerts
|

Epidermal Growth Factor Receptor and Tyrosine Phosphorylation of Estrogen Receptor

Abstract: Activation of estrogen receptor-alpha (ERalpha) by growth factors in the absence of estrogen is a well-documented phenomenon. To study further this process of ligand-independent receptor activation, COS-7 cells without ER were transfected with both ER and epidermal growth factor receptor (EGFR). In the absence of estrogen, epidermal growth factor (EGF) stimulated rapid tyrosine phosphorylation of ER in transfected COS-7 cells. Similarly, in MCF-7 breast cancer cells that have natural expression of ER and EGFR,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
61
0
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(63 citation statements)
references
References 56 publications
1
61
0
1
Order By: Relevance
“…In recent years, much evidence has shown that in multiple cell types under different experimental conditions, steroid receptors directly interact with several signaling effectors and trigger various biological effects. In addition to Src, these effectors include calmodulin (Castoria et al, 1988), the regulatory subunit of the phosphoinositide 3-kinase, p85a (Simoncini et al, 2000;Castoria et al, 2001), Shc (Song et al, 2002), modulator of non genomic activity of receptor (Wong et al, 2002), protein kinase Cz (Castoria et al, 2004), EGF receptor (Marquez et al, 2001;Migliaccio et al, 2005), and many other signaling or signaling-related proteins. Therefore, approaches similar to those followed in this report, that is, recognition of new receptor/signaling effector interactions and identification of new inhibitors of such interactions, could enable us to specifically inhibit different hormone actions mediated by signal transducing pathways in multiple cell types and in different pathological conditions.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, much evidence has shown that in multiple cell types under different experimental conditions, steroid receptors directly interact with several signaling effectors and trigger various biological effects. In addition to Src, these effectors include calmodulin (Castoria et al, 1988), the regulatory subunit of the phosphoinositide 3-kinase, p85a (Simoncini et al, 2000;Castoria et al, 2001), Shc (Song et al, 2002), modulator of non genomic activity of receptor (Wong et al, 2002), protein kinase Cz (Castoria et al, 2004), EGF receptor (Marquez et al, 2001;Migliaccio et al, 2005), and many other signaling or signaling-related proteins. Therefore, approaches similar to those followed in this report, that is, recognition of new receptor/signaling effector interactions and identification of new inhibitors of such interactions, could enable us to specifically inhibit different hormone actions mediated by signal transducing pathways in multiple cell types and in different pathological conditions.…”
Section: Discussionmentioning
confidence: 99%
“…A well-studied phosphorylation site in ER-a is Ser 118 (28). Both estrogen and EGF are able to enhance phosphorylation of ER-a at Ser 118 residue in various cell lines (28,35,43,45,66). EGF-induced acute phosphorylation of ER-a may be associated with the molecular cross-talk between ER and EGFR in MCF-7 cells (35,36).…”
Section: Discussionmentioning
confidence: 99%
“…Both estrogen and EGF are able to enhance phosphorylation of ER-a at Ser 118 residue in various cell lines (28,35,43,45,66). EGF-induced acute phosphorylation of ER-a may be associated with the molecular cross-talk between ER and EGFR in MCF-7 cells (35,36). Consistent with previous studies, our findings indicate that EGF enhances phosphorylation of ER-a at Ser 118 in MCF-7 cells parallel with WISP-2/CCN5 up-regulation (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another potential role player in endometrial cancer aetiology is the epidermal growth factor (EGF). This protein can activate ESR1 and acts as a potent mitogen for epithelial cells (Nelson et al, 1991;Ignar-Trowbridge et al, 1992;Curtis et al, 1996;Dickson and Lippman, 1998;Marquez et al, 2001). We intended to study common variation in both the ESR1 (MIM 133430) and EGF (MIM 131530) genes in relation to endometrial cancer risk, myometrial invasion and endometrial cancer survival.…”
mentioning
confidence: 99%